Community‐Based Health Insurance scheme implementation in Ethiopia: A mini‐review on the experience and its implementation process. Issue 4 (10th August 2022) - Tefera, Yonas Getaye; Ayele, Asnakew Achaw
Abstract: The Community‐Based Health Insurance (CBHI) scheme was introduced in Ethiopia to overcome the population's over‐reliance on direct out‐of‐pocket expenditures for health care and the associated low level of health service utilization. CBHI is an advance payment arrangement, established on the household level, and targeted mainly at informal sectors in rural areas. After a successful 3‐year pilot implementation, the Ethiopian government decided to expand the CBHI scheme implementation. It has received wide interest among community members, especially those living with chronic diseases and perceived impaired family health status. Low enrollment to the scheme was the barrier to its initial expansion due to limited awareness and misconceptions about the program, financial constraints to paying premiums, and dissatisfaction with the health services. The evaluation of CBHI scheme implementation and future implications in Ethiopia could be better seen from both the learning experience during the implementation process and achievements of the policy objectives. Key points: Community‐Based Health Insurance (CBHI) was introduced in Ethiopia to reduce out‐of‐pocket expenditures, ensure citizens' access to and utilization of essential health services Various facilitators and barriers to the CHBI scheme enrollment were identified The CBHI policy's success in Ethiopia could be better seen from the perspective of both the learning experiences during the implementation process and achievement of its objectives. 摘要: 埃塞俄比亚引入了以社区为基础的健康保险（CBHI）计划，以克服人口对用于医疗的直接自付费用的过度依赖以及相关的医疗服务使用程度低的问题。CBHI是一种预付款安排，其建立在家庭层面，主要针对农村地区的非正式部门。经过3年的成功试点后，埃塞俄比亚政府决定扩大CBHI计划的实施范围。它引起了社区成员的广泛兴趣，特别是那些患有慢性病和被认为家庭健康状况受损的人。由于对该计划的认识不足和误解、支付保费的财务限制以及对医疗服务的不满，该计划的低参与率曾是其最初扩张的障碍。对埃塞俄比亚CBHI政策成功和未来影响的判断可能不得不考虑具有广泛前景的学习经验和政策目标的成就。 Resumen: El plan de seguro de salud basado en la comunidad (CBHI) se introdujo en Etiopía para superar la dependencia excesiva de la población de los gastos de bolsillo directos para la atención de la salud y el bajo nivel asociado de utilización de los servicios de salud. CBHI es un acuerdo de pago por adelantado, establecido a nivel del hogar y dirigido principalmente a los sectores informales en áreas rurales. Después de una exitosa implementación piloto de 3 años, el gobierno etíope decidió expandir la implementación del esquema CBHI. Ha recibido un gran interés entre los miembros de la comunidad, especialmente aquellos que viven con enfermedades crónicas y perciben un estado de salud familiar deteriorado. La baja inscripción en el esquema fue la barrera para su expansión inicial debido a la poca conciencia y los conceptos erróneos sobre el programa, las limitaciones financieras para pagar las primas y la insatisfacción con los servicios de salud. Los juicios sobre el éxito de la política CBHI y las implicaciones futuras en Etiopía pueden tener que considerar tanto la experiencia de aprendizaje con perspectivas de amplio alcance como los logros de los objetivos de la política.